The elements of style by William Strunk, Jr. ; with revisions, an introd., and a chapter on writing by E.B. White.. - Strunk, William, 1869-1946. (Macmillan, 1979)
Whether you write letters, term papers, or novels, this famous manual can help you communicate more effectively.